Development Strategy Of Coastal Village Based On Marine Tourism Potential In Munjungagung Village, Tegal Regency, Central Java Province - Beni Sabdo Nugroho; Frida Purwanti; Pujiono Wahyu Purnomo; Atrasina Adlina (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2022)
ABSTRACTOne of the coastal resource that has considerable potential but has not been appropriately managed is marine ecotourism resources. Munjungagung Village has beautiful beaches and is never empty of visitors during holidays. There is also a Fishing and Diving Spot. It can be a potential for marine ecotourism and has an excellent opportunity to develop into mainstay tourism. It is hoped that it can improve the community welfare. This research aimed to study the Coastal Village's plan, which was developed based on the potential for marine tourism in Munjungagung Village. This research used the descriptive method and was conducted from April to November 2021 to determine the potential for marine tourism, psychographics of tourists, the carrying capacity of the area, and a strategic development plan. The data were analyzed using Tourism Suitability Index (TSI), Regional Carrying Capacity, and SWOT. It showed that the tourist sites were still suitable for beach tourism activities, snorkeling, and diving. The TSI of this site is 94.05% which is interpreted as very suitable. The site also fulfills the carrying capacity of tourism, except during the peak holiday season. Based on the calculation, this site can accommodate 300 people per day, and 8 people for snorkeling and diving in an area of 5.0 ha. Keywords: Marine Ecotourism, Regional Suitability, Carrying Capacity, Larangan Beach